2017
DOI: 10.4067/s0718-95162017005000038
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of municipal organic waste among others composting techniques improves N cycling through waste-soil-plant continuum

Abstract: This study aimed to examine the effect of composting techniques of municipal organic solid waste (MSW) for (i) total carbon (C), nitrogen (N) losses, and changes in its chemical characteristics during composting phase and (ii) value of the composted materials as fertilizer when applied to vegetables. Treatments included: aerobic composting (AC), anaerobic composting (ANC), co-composting (CC) and open dumping (OD) for 4 months.During the composting phase, about 61, 50, 35, and 13% of the initial N was lost from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Our results showed that the AC had the lowest nitrogen losses and that the differences between the AC and FC as well as MC were significant ( p < 0.05). However, Shah et al [26,71] concluded that AnC treatment resulted in the lowest amount of N losses in their study. The main cause of this difference was the different composting conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Our results showed that the AC had the lowest nitrogen losses and that the differences between the AC and FC as well as MC were significant ( p < 0.05). However, Shah et al [26,71] concluded that AnC treatment resulted in the lowest amount of N losses in their study. The main cause of this difference was the different composting conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Larger pools of MBC and MBN were produced by the combination of biochar and N fertilizer, especially in the top soil (0-10 cm) layer [34]. In the second year higher microbial activities was recorded in the treatment which is treated with poultry manures it may be due to decomposition of PM lesser than that of Compost [35].…”
Section: Discussionmentioning
confidence: 96%
“…The different manure treatments were used to capture the effects of the volatilization of nutrients due to solar heating (temperature). An impermeable plastic sheet (0.15-mm-thick polyethylene film) was used as lining underneath the manure ( 36 ).The cattle manure was stored for 5 months. Manure collection was completed in 3 days to eliminate time effects.…”
Section: Methodsmentioning
confidence: 99%